The Effectiveness of Think Pair Share Strategy Based on Arabic Scrabble Media in Improving Writing Skills Students - Zulaini, Nabilla Nurbaiti; Rochman, Taufiq; Hasaniyah, Nur (JURNAL IJ-ATL, 2025)
Developing Arabic writing skills, particularly in imla’ manzhur (dictated visual writing), requires effective strategies that engage students in both linguistic structure and practical application. This study investigates the implementation of the Think Pair Share (TPS) strategy supported by Arabic Scrabble media as an alternative approach to enhance students’ writing proficiency. Utilizing a quantitative experimental method, the research integrates observation, interviews, tests, and documentation to explore how cooperative learning combined with interactive media can improve students’ mastery of Arabic script, vocabulary, and sentence formation. The findings reveal that the TPS strategy, through its structured phases of individual thinking, peer discussion, and group sharing, provides an active and reflective learning environment. The addition of Arabic Scrabble as a visual and kinesthetic aid enriches students’ engagement with Arabic orthography and supports collaborative vocabulary construction. The study concludes that this integrated strategy fosters improved accuracy in connected writing and motivates learners to participate more confidently in Arabic writing activities.